My Haiku Practice - Dwyer, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
I was busy. Often, I was not mindful of the present moment. Too often I was thinking ahead to the next thing on my list. So I began to write one haiku each day. I thought it might help to become more present, mindful, and responsive. In this essay, I describe my haiku practice. At first, I wanted to save my haiku and arrange them by seasons, but that didn’t work. So I arranged them in these categories: walk to work; nature and human nature; young and old; married life; modern life; computers, AI, and the Internet; academic life; medical world; pandemic life; retirement; political life; spiritual practice; death; and attitude toward death. I explain these categories by giving examples of the haiku that I wrote. I also add a short, tentative conclusion that refers back to my spiritual aims: to become more present, mindful, and responsive. My practice did help me to become more present and mindful, but I’m not sure that I’m any more responsive. I believe that to become more responsive, I will need to develop new habits — new ways of inhabiting the world. I conclude with steps that might help me to become more responsive.